In situ/operando techniques for characterization of single-atom catalysts - Li, Xuning (2020)
In situ/operando characterization techniques are powerful to provide fundamental information about molecular structure–activity/selectivity relationships for various catalytic systems under controlled condition. However, the lack of model catalyst, as the major obstacle for deeper understanding on the nature of active sites and reaction mechanisms, hinders the further advancements in catalysis. Fortunately, the rapid development of single-atom catalysts (SACs) offers us new opportunities for capturing the reaction intermediates, identifying the active sites, and even monitoring the dynamic behaviors of both the geometric structure and electronic environment of the catalytic sites at atomic scale. In this Perspective, the recent advances on the in situ/operando characterization techniques including X-ray absorption spectroscopy, scanning tunneling microscopy, Fourier-transform infrared spectroscopy, among other methods, for the characterization of SACs are thoroughly summarized. The results from these in situ/operando measurements reveal the crucial role of SACs as model systems for sharpening our understanding on the nature of catalytic sites. Furthermore, the challenges and outlooks in developing in situ/operando techniques for single-atom catalysis are discussed.